Establishment, Expansion, and Outcomes at a Student-Run Free Clinic Serving People Experiencing Homelessness - Eames, Bradley; Valere, Lynn-Caelle; Keith, Daniel; Kudapa, Divya; Park, Yongho; Thokalath, Adrien; Wilson, Hannah; Hernandez, Caridad (Journal of Student-Run Clinics, 2025)
The number of student-run free clinics (SRFCs), which offer free care to persons and communities with limited healthcare access, has increased nationwide in recent years. The University of Central Florida College of Medicine’s Chapman Compassionate Care Clinic (CCCC), an SRFC, was founded in 2018 and provides skin and wound care to a growing number of people experiencing homelessness in downtown Orlando, Florida. In this paper, we briefly describe the founding and operation of CCCC. A chart review of all patients seen since the program’s inception was performed, and descriptive statistics are detailed to characterize the patients, dermatologic conditions, and comorbidities encountered and to assess the potential impact of CCCC. This chart review showed diverse acute and chronic needs among CCCC’s population and revealed that the clinic engaged patients who typically utilize other traditional sources of healthcare services at lower levels, potentially due to the clinic’s strategic co-location of services. We describe the process of developing co-located services through partnerships with existing community organizations in an effort to limit barriers to healthcare.